2016
DOI: 10.3892/etm.2016.3762
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of eNOS overexpression against ischemia/reperfusion injury in small-for-size liver transplantation

Abstract: Ischemia/reperfusion (I/R) injury can occur during small-for-size liver transplantation, resulting in delayed graft function and decreased long-term graft survival. The aim of the present study was to evaluate the effects of genetic overexpression of endothelial nitric oxide synthase (eNOS) in protecting hepatocytes against I/R injury in a rat model of small-for-size liver transplantation. L02 liver cells were transfected with the eNOS gene using an adenovirus (Ad-eNOS). eNOS expression was detected using quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In hypoxic–ischemic conditions, as occurs also in organs during cold storage, eNOS promotes vasodilation increasing blood flow, and this event is responsible for increasing graft preservation [ 19 ]. Recently, Zhang et al reported that eNOS-derived NO production significantly attenuates hepatic I/R injury, suggesting that NOS overexpression may constitute a promising therapeutic approach to prevent liver I/R injury following liver transplantation [ 20 ]. Russo et al documented that the addition of simvastatin to the storage solution increased eNOS content, prevented liver damage, and improved endothelial dysfunction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxic–ischemic conditions, as occurs also in organs during cold storage, eNOS promotes vasodilation increasing blood flow, and this event is responsible for increasing graft preservation [ 19 ]. Recently, Zhang et al reported that eNOS-derived NO production significantly attenuates hepatic I/R injury, suggesting that NOS overexpression may constitute a promising therapeutic approach to prevent liver I/R injury following liver transplantation [ 20 ]. Russo et al documented that the addition of simvastatin to the storage solution increased eNOS content, prevented liver damage, and improved endothelial dysfunction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a NO releasing hydrogel has been documented to enhance the therapeutic effects of mesenchymal stem cell therapy for hind limb ischemia [ 89 ]. In this context, overexpression of eNOS was reported to be protective against ischemia/reperfusion injury [ 90 ]. The eNOS-derived NO was proven to be essential for both early and late vascular recovery in response to hind limb ischemia [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated the hepatoprotective effect of genetic eNOS overexpression in small-for-size liver transplantation and illustrated the importance of promoting eNOS expression for hepatoprotection[ 61 ]. However, there is insufficient evidence for a protective effect of eNOS overexpression, and evidence that eNOS overexpression is detrimental to HIRI[ 62 ].…”
Section: Regulating Inos and Enos Expression To Protect Hirimentioning
confidence: 99%